The use of Anakinra in treatment of calcium pyrophosphate crystal deposition disease: Analysis of own experience and a literature review - M. S. Eliseev; E. V. Cheremushkina; E. L. Nasonov (Научно-практическая ревматология)
Calcium pyrophosphate crystal deposition disease (CPPD) is a disease caused by the deposition of calcium pyrophosphate crystals, mainly in the articular cartilage, and often manifests as severe acute or chronic arthritis. Therapy given in such cases with non-steroidal anti-inflammatory drugs, colchicine, methotrexate and glucocorticoids is often effective. In these cases, the possibility of prescribing biological drugs, primarily interleukin 1 (IL-1) inhibitors, is being considered. The article analyzes the experience of using Anakinra, an IL-1 receptor antagonist, registered in the Russian Federation in 2021, in 5 patients with persistent arthritis in CPPD. The article also presents an analysis of data from key studies on the use of the drug in patients with CPPD.